PENGUKURAN KINERJA INSTANSI PEMERINTAH DALAM PERSPEKTIF VALUE FOR MONEY - Suwandi, Mega Maranda; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to find out and to analyze the performance of the Department of Archive andLibrary of Surabaya City is measured by using value for money approach, i.e.: economy, efficiency andeffectiveness. The research method has been carried out by using descriptive qualitative and the source of data isthe primary and the secondary data.The result of the analysis and the discussion shows that in determiningeconomic performance is done by considering input and market price. The efficiency performance is reviewed byusing the comparison between the output that has been generated and the input that has been used (cost ofoutput). The effectiveness performance is measured by comparing the target of SKPD which has carried out thenew pattern system and the visitors who have visited the library of Surabaya city and the target realization. Thedevelopment of performance measurement model in value for money perspective requires the development ofindicator which includes input, output, and outcome. So, the performance indicators i.e.: economy, efficiency,and effectiveness are relevant with the objectives of activities and work program.Keywords:Value for money, economy, efficiency, effectiveness